Pollution by polar pesticides and pharmaceuticals and risk assessment in surface water bodies along the French Mediterranean coast: Complementarity of target and non-target screenings - Nicolas Martin; Geoffroy Duporté; Etienne Lemaire; Andrés Sauvêtre; Marine Bertrand; David Rosain; Elena Gomez; Emilie Farcy (Environmental Chemistry and Ecotoxicology)
Anthropogenic activities are the source of a wide range of organic micropollutants (OMPs) found in all water bodies. Among them, pharmaceuticals and pesticides are the most found in watercourses and their impacts on non-target organisms have already been documented. Pesticides are well monitored in the river-lagoon continuum with their integration into the European water frame directory (WFD). However, their presence may co-occur with pharmaceuticals from wastewater treatment plants discharges in watersheds. Their monitoring and risk assessment is an important knowledge gap in the WFD strategy. In this study, we used polar organic chemical integrative samplers to assess the concentrations of pharmaceuticals and pesticides (parent compounds and transformation products) in water bodies of the French Mediterranean coast and to assess environmental risk during late spring-early summer. Internal concentration of pharmaceuticals in mosquitofish was assessed to evaluate fish pharmaceutical burden. A non-target screening method was used to complementary describe OMPs cocktail in water. Twenty-nine pharmaceuticals and 12 pesticides were quantified using a targeted approach. Six pesticides and 23 pharmaceuticals were further detected using a non-target screening. Pharmaceuticals concentration and associated environmental risk were higher than pesticides ones in mixed-used watersheds, although their risk assessment was limited by the low number of ecotoxicological data available for pharmaceuticals. Six pharmaceuticals were found in fish tissue, increasing potential biological impacts for this trophic level. This study highlighted the importance of monitoring concentrations of pharmaceutical products in the environment and increasing the ecotoxicological testing effort to improve risk assessment.